2019
DOI: 10.1107/s2052520619008357
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial defects in the van der Waals gap of Bi2Se3

Abstract: Bi2Se3 is a thermoelectric material and a topological insulator. It is slightly conducting in its bulk due to the presence of defects and by controlling the defects different physical properties can be fine tuned. However, studies of the defects in this material are often contradicting or inconclusive. Here, the defect structure of Bi2Se3 is studied with a combination of techniques: high-resolution scanning transmission electron microscopy (HR-STEM), high-resolution energy-dispersive X-ray (HR-EDX) spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 85 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…Bi interstitial defects in the van der Waals gaps of Bi 2 Se 3 crystals have also been identified by HR-STEM measurements. 28 A reasonable assumption is to assign the adatoms as Bi adatoms that are formed according to the first mechanism mentioned above.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bi interstitial defects in the van der Waals gaps of Bi 2 Se 3 crystals have also been identified by HR-STEM measurements. 28 A reasonable assumption is to assign the adatoms as Bi adatoms that are formed according to the first mechanism mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Bi interstitial defects in the van der Waals gaps of Bi 2 Se 3 crystals have also been identified by HR-STEM measurements. 28 A reasonable assumption is to assign the adatoms as Bi adatoms that are formed according to the first mechanism mentioned above. However, experimental and simulated STM images of the adatoms cannot unequivocally distinguish between Bi and Te adatoms, implying the possibility that the adatoms are Te adatoms cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of TEM, it was suggested [9] that lateral movement of the dopants (due to the low diffusion barrier [8]) inside the vdW gap at room temperature precludes an observation. However, a recent TEM study of native defects in Bi 2 Se 3 demonstrated that Bi atoms inside the vdW gap can be observed [15]. STM data of Cu-doped Bi 2 Se 3 thin-films grown by molecular beam epitaxy showed Cu atoms inside the quintuple layer, but no direct evidence of Cu inside the vdW gap [8].…”
Section: Introductionmentioning
confidence: 94%